2019
DOI: 10.3390/antiox8080283
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Total Polyphenol Content and Antioxidant Activity of Chocolate Obtained from Roasted and Unroasted Cocoa Beans from Different Regions of the World

Abstract: The polyphenol content of cocoa beans and the products derived from them, depend on the regions in which they are grown and the processes to which they are subjected, especially temperature. The aim of the study was to compare the total content of polyphenols and antioxidant activity of chocolates obtained from roasted and unroasted cocoa beans. The chocolates produced from each of the six types of unroasted beans and each of the five types of roasted beans were investigated. The seeds came from Ghana, Venezue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 45 publications
4
46
0
3
Order By: Relevance
“…Cocoa is also rich in minerals: potassium, phosphorus, copper, iron, zinc, and magnesium [18]. The nutritional values of cocoa and two types of chocolate appear in Table 1 [13,19,20].…”
Section: Nutritional Aspectsmentioning
confidence: 99%
“…Cocoa is also rich in minerals: potassium, phosphorus, copper, iron, zinc, and magnesium [18]. The nutritional values of cocoa and two types of chocolate appear in Table 1 [13,19,20].…”
Section: Nutritional Aspectsmentioning
confidence: 99%
“…(3). The EFSA (European Food Safety Authority) recognized to chocolate and cocoa powder as an important source of polyphenols with outstanding properties for health (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Proanthocyanins, catechins, or flavan-3-ols and anthocyanins are the major flavonoids in cocoa beans, with 58, 37, and 4 percent (%) in content, respectively. (3,4). The content and composition of polyphenols in cocoa beans dependent on many factors such as genotype, origin, type of clone, growth conditions, fermentation, drying, and roasting process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cocoa from Madagascar was selected because Bruna et al [24], comparing the content of polyphenols in cocoa husks from different countries (Ghana, Madagascar, Ecuador, Trinidad, and Venezuela), found that Madagascar husks were the richest. The cocoa from Costa Rica was chosen because compared to that from other countries (Ivory Coast, Venezuela, Samoa, Trinidad, Brazil, Ghana, Ecuador, Jamaica), it was found to be particularly rich in epicatechin [25][26][27][28].…”
Section: Cocoa Bean and Husk Phenol Extractionmentioning
confidence: 99%